Mutualism supports biodiversity when the direct competition is weak - Alberto Pascual-García (Nature Portfolio, 2017)
Theoretical ecologists have made disparate predictions regarding the relationship between mutualism and stability. Here, Pascual-García and Bastolla develop a theoretical framework showing that model mutualistic interactions promote structural stability when competition is weaker than a threshold depending on network architecture.